POLITIK HUKUM PERTAMBANGAN MINERAL DAN BATUBARA SAAT BERLAKU UNDANG-UNDANG NOMOR 23 TAHUN 2014 TENTANG PEMERINTAHAN DAERAH - Fine Ennandrianita; Isharyanto; I Gusti Ayu Ketut Rachmi Handayani (Program Pascasarjana Fakultas Hukum Universitas Sebelas Maret Surakarta, 2018)
AbstractThis paper discusses the legal politics of mineral and coal mining, as well as the authority of the goverment in managing the natural resources of mineral and coal mining. Mineral and coal mining is a non-renewable natural resource, so for the sake of sustainability the government's role in management, coaching and supervision is needed. Major Changes occured since the enactment of law No. 23 of 2014 on Regional Goverment which regulates the distribution of goverment affairs. The existence of the Law makes the authority of the management of mineral and coal mining in the Regional Government of Regency or City to be abolished This research is a prescriptive legal research with a legal approach and a conceptual approach.This paper is a presciptive legal research with approach of law and conceptual approach. The technique of collecting legal materials in this paper is literature study. The technique of analysis of legal materials used is the method of deduction. This paper concludes the existence of disharmonization between sectoral regulations and local government laws in 2014 and the legal consequences of the enactment of the Regional Government Law in the form of (i) institutional change, (ii) personnel handover, funding, facilities and infrastructure, (P3D), (iii) amendment of laws and regulations.Keywords: legal politics, mineral and coal mining, patient, enactment of law No. 23 of 2014 on Regional Goverment AbstrakTulisan ini membahas politik hukum pertambangan mineral dan batubara serta kewenangan pemerintah dalam mengelola sumber daya alam pertambangan mineral dan batubara. Pertambangan mineral dan batubara merupakan sumber daya alam yang tidak dapat diperbaharui, sehingga demi keberlangsungan diperlukan peran pemerintah dalam hal pengelolaan, pembinaan dan pengawasan. Perubahan besar terjadi sejak diberlakukan Undang-Undang Nomor 23 Tahun 2014 tentang Pemerintahan Daerah, yang mengatur mengenai pembagian urusan pemerintahan. Keberadaan Undang-Undang tersebut membuat kewenangan pengelolaan pertambangan mineral dan batubara di Pemerintah Daerah Kabupaten/ Kota menjadi hapus. Penelitian ini merupakan penelitian hukum yang bersifat preskiptif dengan pendekatan undang-undang dan pendekatan konseptual. Teknik pengumpulan bahan hukum studi pustaka dan teknik analisis bahan hukum metode deduksi. Hasil tulisan ini menyimpulkan adanya disharmonisasi antara peraturan perundangan sektoral dengan UU Pemda 2014 dan adanya konsekuensi hukum terhadap pemberlakuan UU Pemda berupa (i) perubahan kelembagaan; (ii) serah terima personil, pendanaan , sarana dan prasarana, dan dokumen (P3D); (iii) perubahan peraturan perundang-undangan.Kata kunci: politik hukum, pertambangan mineral dan batubara, undang-undang nomor 23 tahun 2014 tentang pemerintahan daerah.